2023
DOI: 10.1021/acsmaterialslett.3c00452
|View full text |Cite
|
Sign up to set email alerts
|

CoCr2O4 Nanoparticles with Abundant Oxygen Vacancies: A New Photothermal Platform for Efficient Solar Evaporation

Abstract: Solar-driven interfacial photothermal evaporation has been recognized as a green, economical, and efficient water purification technique in recent years, and it is one of the most promising methods to realize the supply of high-quality freshwater resources. The key and challenge to achieving a superior water evaporation rate is to explore novel stable materials with high light absorption and photothermal conversion efficiency. In the present work, CoCr2O4 nanocrystals containing a large number of oxygen vacanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The hydrophilic nature of the solar evaporator ensures an adequate water supply for the water vapor generation process, which is necessary for efficient solar evaporation. 39 Fig. 3H shows that the water droplets were absorbed by the CS/MXene aerogel within 1.3 s, facilitating water permeability.…”
Section: Resultsmentioning
confidence: 97%
“…The hydrophilic nature of the solar evaporator ensures an adequate water supply for the water vapor generation process, which is necessary for efficient solar evaporation. 39 Fig. 3H shows that the water droplets were absorbed by the CS/MXene aerogel within 1.3 s, facilitating water permeability.…”
Section: Resultsmentioning
confidence: 97%
“…It is assumed that the multilevel porous structure can enhance the light absorption ability of the film due to the rich pore channels for strong light reflection and scattering. For typical semiconductors such as metal oxides, there are reports that Fe, Cr, Co and V can enhance the optical absorption of visible light. Ti, Mo and Cu elements can enhance the optical absorption under ultraviolet light, while Ni can enhance the absorption of near-infrared light . It is hypothesized that a similar effect also exists in our np-HEOs.…”
mentioning
confidence: 77%
“…Recently, there has been a growing concern in cellulose nanofiber (CNF)-based hydrogels for SSGs due to their numerous advantages, including a high specific surface area, abundant sources in nature, hydrophilia, renewable, environmental friendliness, and biodegradability, which show vast application prospects in elastic hydrogels, ionic conduction, and biomedicine. In addition, CNF-based hydrogels have been widely reported in the field of SSGs. For example, Xu et al have reported a 3D photothermal aerogel composed of reduced graphene oxide (rGO), sodium alginate (SA), and cellulose fibers derived from rice straw, which has exhibited an evaporation rate of 2.25 kg m –2 h –1 with an energy conversion efficiency of 88.9% under one sun illumination. Han and coworkers presented Janus cellulose nanofibril-based aerogels consisting of MXenes, which showed an evaporation rate of 2.287 kg m –2 h –1 under one sun.…”
Section: Introductionmentioning
confidence: 99%